HUBUNGAN IMPLEMENTASI NILAI-NILAI AKHLAK DENGAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA PUTRI DI DESA RENDENG RW 2-5 KABUPATEN KUDUS - Muhammad Abdur Rozaq; Endang Pujiyati (Universitas Muhammadiyah Kudus, 2017)
Background: Knowledge of adolescent reproductive health is still very low evidenced 83.7% of adolescent reproductive health and the lack of understanding of just 3.6% who know the importance of reproductive health. So also with the limited knowledge of adolescents about reproductive health often leads to premarital sex acts. City teenagers are increasingly daring sexual intercourse before marriage. Objective: To determine the relationship of adolescent dating behavior with adolescent premarital sexual incident in the village of the district Rendeng Kudus. Methods: This study was correlational. The approach used in this study was cross sectional. The population in this study were young in the village Rendeng totaling 140 people. Sample of 58 people. Data analysis using chi square.Results of the research Most teens have not suit the application value - the value of religion as many as 35 people (60.3%) and the appropriate application of value - the value of religion as much as 23 people (39.7%). Most teens have a negative sexual behaviors as many as 36 people (62.15) and was positive in 22 (37.9%). There is a relationship Application values of Islam with Genesis Premarital Sexual Teen in Village Rendeng RW 2-5 Kudus Regency (p value = 0.001).